PERAN KOMUNIKASI KELOMPOK TANI PADI SAWAH DALAM PENINGKATAN KAPASITAS ANGGOTA DI KELURAHAN BARGUGA KECAMATAN BARUGA KOTA KENDARI - Aron, Muhammad; Wunawarsih, Ima Astuty; Lasinta, Megafirmawanti (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The objective of this study is to examine the role of farmer group communication on the capacity of members of the paddy rice group in Baruga Village, Baruga District, Kendari City. The population under investigation consisted of all members of the paddy rice farmer group, which numbered 16 groups with a total membership of 160 farmers. The research sample was determined using the Slovin formula, with a confidence level of 90% or 10% of the total population sampled. This resulted in a sample size of 54 respondents. Data collection techniques employed survey methods, interviews, and documentation using research instruments in the form of questionnaires. The research employed a quantitative approach, utilizing quantitative descriptive analysis through the application of the class interval formula and the Spearman rank correlation formula, with the assistance of the SPSS software version 26. The findings indicated that the communication role within the rice paddy farmer group in Baruga Village, Baruga District, Kendari City, with respect to the information aspect, was categorized as "available," the learning aspect was categorized as "active," and the intensity of discussion was categorized as "frequent." The capacity of paddy rice farmer group members for the knowledge aspect is in the knowing category, the attitude aspect is in the adequate category, and the skill aspect is in the skillful category. The relationship between the role of farmer group communication in increasing the capacity of members of the paddy rice farmer group is evident when examining the role of information access to attitudes, the role of learning classes to knowledge, attitudes, and skills, and the role of discussion intensity to knowledge, attitudes, and skills. Each of these relationships is significant, while the role of information access to knowledge and skills does not demonstrate a significant relationship.